2021
DOI: 10.1177/17588359211019642
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory indices and clinical factors in metastatic renal cell carcinoma patients treated with nivolumab: the development of a novel prognostic score (Meet-URO 15 study)

Abstract: Background: Despite the survival advantage, not all metastatic renal cell carcinoma (mRCC) patients achieve a long-term benefit from immunotherapy. Moreover, the identification of prognostic biomarkers is still an unmet clinical need. Methods: This multicenter retrospective study investigated the prognostic role of peripheral-blood inflammatory indices and clinical factors to develop a novel prognostic score in mRCC patients receiving at least second-line nivolumab. The complete blood count before the first cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 58 publications
(153 reference statements)
2
59
1
Order By: Relevance
“…Interestingly, despite the difference in the treatment lines between the later-line and first-line treatments and the patients' ethnicity among Japanese and Western populations, the prognostic utility of baseline NLR has been reported to be consistent (20)(21)(22). The present study combined baseline medications with the routinely available NLR at baseline as a novel prognostic score, and an NLR ≥ 3 was assigned 2 points as in previous studies (20)(21)(22). Rebuzzi et al (20) reported that in patients with metastatic renal cell carcinoma who received nivolumab (n = 571) as a second-and further-line setting, the Meet-URO prognostic score of baseline NLR and clinical factors showed a predictive ability for survival outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, despite the difference in the treatment lines between the later-line and first-line treatments and the patients' ethnicity among Japanese and Western populations, the prognostic utility of baseline NLR has been reported to be consistent (20)(21)(22). The present study combined baseline medications with the routinely available NLR at baseline as a novel prognostic score, and an NLR ≥ 3 was assigned 2 points as in previous studies (20)(21)(22). Rebuzzi et al (20) reported that in patients with metastatic renal cell carcinoma who received nivolumab (n = 571) as a second-and further-line setting, the Meet-URO prognostic score of baseline NLR and clinical factors showed a predictive ability for survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Once validated, these parameters could be used in the clinical setting, as they are easily available and do not require additional costs or setup. Hence, NLR was selected for the development of the prognostic score, based on Rebuzzi et al (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, Harrell's concordance statistic was similar to that reported by Buti et al (16). Interestingly, despite the difference in the treatment lines between the later-line and first-line treatments and the patients' ethnicity among Japanese and Western populations, the prognostic utility of baseline NLR has been reported to be consistent (20)(21)(22). The present study combined baseline medications with the routinely available NLR at baseline as a novel prognostic score, and an NLR ≥ 3 was assigned 2 points as in previous studies (20)(21)(22).…”
Section: Discussionsupporting
confidence: 89%
“…Inflammatory indices from peripheral blood have been investigated in combination with other clinical prognostic factors within prognostic models for risk-stratification in several cancer types treated with ICIs, especially the NSCLC [ 91 , 98 , 99 , 100 ]. The interest in prognostic models has also recently been increasing for genitourinary tumours, including RCC [ 101 , 102 , 103 ] and UC [ 63 , 65 , 68 , 95 , 96 , 97 , 104 ].…”
Section: Clinical Factorsmentioning
confidence: 99%